Iberian World: limitrophes civilizations on the epoch of the globalization - Yu Leonardovna Obolenskaya (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2013)
The article analyzes the ethnic-lingvocultural processes in the age of Globalization in one of the most important and interesting civilization — mundo ibérico.